Predstave o skrivnostnih izgonskih krajih bolezenskih demonov na slovenskem - Makarovič, Gorazd (Etnolog. Nova vrsta (Ljubljana), 2016)
Based on healing invocations recorded in the 19th and first half of the 20th centuries, the article outlines and defines contemporary notions of the special places where demons, thought to be responsible for diseases, were magically cast out to.
Keywords: ljudsko verovanje; magija; zdravilstvo; bolezenski demoni; Slovenia; Slovenija; zgodovinski pregledi